Absencing as Attentional Violence and Its Impact on Well-Being - Bianca Briciu (Journal of Awareness-Based Systems Change)
This paper analyzes the impact of absencing on well-being. It explores the source of absencing in the attentional violence created by the logic of internalized capitalism: the belief that one’s self-worth is linked to productivity, the consumerist model of well-being, and the instrumentalization of relationships. The worldview created through the internalization of capitalist values leads to a stress enhancing, alienating way of life with negative consequences for well-being. Attention is diverted away from the wholeness of self and other, from the quality of relationships, creating a social field where individuals relate to themselves, others and the world through the logic of absencing. When this logic dominates the subjective structure of the inner world it reinforces self-optimization and commodified social relations that undermine well-being. Critical awareness of the internalization of capitalism reveals that even transformative approaches for well-being can become instrumentalized by the capitalist logic. This article highlights the importance of a critical lens to understand how mindfulness, and spirituality in organizations can become dominated by a capitalist worldview. It will use presencing in Theory U as a case study of a transformative approach aiming to undermine absencing while being constantly haunted by its influence.